Cultural identity of Beji Village Community in Onggoloco Folktale: ethnographic study of literary anthropology - Rahmah, Annisa Fatati; Wulandari, Yosi (Institut Seni Indonesia Surakarta, 2024)
Globalization and the pressures of urban life have resulted in a cultural identity crisis. This study aims to describe the cultural identity of the Beji Village community in the Onggoloco Folktale by analyzing cultural elements (religion, knowledge systems, arts, and livelihoods) through a study of literary anthropology with an ethnographic approach. This type of research uses a qualitative descriptive method. This research was conducted in May-June 2024 in Beji Village, Ngawen, Gunung Kidul, Special Region of Yogyakarta. Data collection through participant observation, interviews, and documentation. Interview data collection using the purposive sampling method with five respondents who are forest and cultural conservation figures. The results of the research found the cultural identity of the Beji Village community in the Onggoloco folktale, namely belief in ancestors, having knowledge of nature conservation, preserving the arts, and making a living as farmers. The Onggoloco folktale strengthens the cultural identity of the Beji Village community by teaching people to always preserve culture. This research contributes to the development of literary anthropology theory. The practical aspect of this research is used as a learning resource in schools related to folklore. Further research is needed that is of a developmental or in-depth nature.